Efficiency of certain insecticides against the black vine thrips, Retithrips syriacus (Mayet) (Thysanoptera: Thripidae) under laboratory and field conditions - Abdu-Allah, G. M.; Abd-Ella, A. A. (Journal of Phytopathology and Disease Management, 2017)
The quantity and quality of grapevine fruit is very important to local and export productions. Black vine thrips (BVT), Retithrips syriacus (Mayet) (Thripidae: Thysanoptera) injured the leaves from seedling to the blooming fall. Insecticides are the main strategy to grapevine insect control. There is a little information about the susceptibility of BVT to insecticides. This study carried out to test the potency and residual activity of six insecticides with different mode of action under laboratory and field conditions. The LC50 values for leaf dip after 24 hours with the insecticides were different. The emamectin benzoate was the most toxic against nymphs, and teflubenzuron was the least one, LC50s value decreased significantly after 48, 72 hours post treatments. For teflubenzuron, the LC50 values recorded were 11900, 7.05, 2.58 µg a.i./ ml after 24, 48 and 72 hours from treatment respectively. Based on the laboratory potency ratios, emamectin benzoate , malathion, and mineral oil showed higher effect against nymphs than adults by 3.11, 1.79, 1.18 folds after 24 hours, being 1.63, 12.73 folds for emamectin benzoate and teflubenzuron after 48 hours, and 1.68 for teflubenzuron after 72 hours. King Roby grapevine variety showed the most significant susceptibility to thrips infestation, while the Flaim was the most tolerant one. Emamectin benzoate was the highest in reduction ratios of nymphs thrips, where 92.30, 93.19 and 93.83% reduction at Flaim, Banaty, and King Roby varieties respectively. These results could be used in integrated pest management (IPM) programs for thrips control in grapevine.